“Law and Development” in the Conflict of Theoretical Approaches - Mohammad Jalali; Ehsan Mouhebati (پژوهشهای حقوقی)
The study of law and development coincided with other issues of development in the twentieth century, and the first and most important question that occupied the minds of jurists was whether law and development are fundamentally related, and if the answer is yes What would be the relationship like in the development process? There are two general approaches to the relationship between law and development: the first group considers development as a function of other elements by assuming law as a dependent knowledge. According to this category, development and its components determine the rules and norms of each society's legal system. In contrast, law has no power to influence the development process but rather becomes flexible according to economic growth, political will, or cultural context. Another group tried to show the independence of law from the other components of development by questioning about the subordination of law. Everyone has not followed the same path, but someone introduced law as an instrument for development and another as a framework for it. As the concept of human development expanded in the 21st century, the relationship between law, and development took on a new form and development was closely linked to the logic of law, ie justice, and law, in addition to its instrumental and institutional role, converted to one of the goals of development.